If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 2(x + 3) = -1x + -6 Reorder the terms: 5 + 2(3 + x) = -1x + -6 5 + (3 * 2 + x * 2) = -1x + -6 5 + (6 + 2x) = -1x + -6 Combine like terms: 5 + 6 = 11 11 + 2x = -1x + -6 Reorder the terms: 11 + 2x = -6 + -1x Solving 11 + 2x = -6 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 11 + 2x + x = -6 + -1x + x Combine like terms: 2x + x = 3x 11 + 3x = -6 + -1x + x Combine like terms: -1x + x = 0 11 + 3x = -6 + 0 11 + 3x = -6 Add '-11' to each side of the equation. 11 + -11 + 3x = -6 + -11 Combine like terms: 11 + -11 = 0 0 + 3x = -6 + -11 3x = -6 + -11 Combine like terms: -6 + -11 = -17 3x = -17 Divide each side by '3'. x = -5.666666667 Simplifying x = -5.666666667
| 0=t^2+t-6 | | a+5=-16 | | -3(5+7p)=33-5p | | -2(x+7)=4x-7 | | -4=13.7 | | 15-3x=12-5x | | 4w(w-6)-2w^2=2w^2+8w-4 | | 2+3n=0.8n+18 | | 14-x=3x-2 | | x^3+5x^2+16x+80=0 | | 4/28=x/147 | | -7(x-6)-8=-5x+40 | | 5W+W=36 | | h=9(8m-9r) | | 6(-6-5)-6=0 | | ln(x+11)+ln(x-3)=2lnx | | 0=a^2-18a+72 | | 4x+6=-7x-7 | | -15t^2+60t=0 | | 5t+6-8t=30 | | 24t^2+19t+2=0 | | .25p+7=3 | | (2x^2-5x-3)=0 | | 2q+30=6-4q | | 50x=20x+10 | | 3x+5+6x=113 | | 50x=20x+30 | | x-2+25=66-2+3x | | 6p-2(p+6)=20 | | 0.5d-8=3 | | -4b+40=-4(2b-5) | | -10-0.5x=-27.5 |